Borderzones and the politics of irregularisation: the Interim Federal Health Program and Toronto's everyday places of healthcare. (2018) - Connoy, Laura
Engaging with the concept of borderzones, this article critically analyses the irregularisation of refugee claimants residing in Toronto, Ontario, Canada. Specifically, attention is placed on the Interim Federal Health Program (IFHP), a federal health insurance program provided to refugee populations, and how it was experienced in everyday healthcare places. Drawing on semi-structured interviews with doctors, lawyers, social workers, and refugee claimants, this article empirically demonstrates irregularising bordering practices within these everyday places, and how refugee claimants and allies challenged such practices through, what I term, acts of liberating irregularity. Overall, this article sheds new light on the role of borders in the processes and politics of irregularisation within the Canadian asylum context.